A Single Phase Active Front-End Converter for Unity Power Factor - Murdianto, Farid Dwi; Sudiharto, Indhana; Nizar, Ahmad Hisam (Jurnal Rekayasa Elektrika, 2025)
A rectifier is an electronic circuit that converts Alternating Current (AC) into Direct Current (DC). This circuit is very important in many electronic applications, especially in power supplies, battery chargers, and other equipment requiring a DC power supply. Conventional rectifiers use diodes or thyristors as rectifying components. Although a rectifier that uses a diode is generally effective and easy to apply in converting AC to DC, the diode or thyristor component has several drawbacks when used as a rectifier, namely the low power factor on the supply side. To overcome these deficiencies, this paper presents the topic of front-end converter which uses Insulated Gate Bipolar Transistor (IGBT) components as a substitute for diode and thyristor components. IGBT is an active component so a SPWM signal is needed to regulate this IGBT so that it can work. In this front-end converter, to achieve unity power factor results on the supply side, SPWM is used so that it can adjust the current waveform on the supply side to be in phase with the voltage waveform on the source side. The front-end converter presented in this paper has also added the load on the AC side to prove the work of the Front-End Converter.